The Petacomp Machine - A MIMD Cluster for Parallel Pattern-mining - Birkeland, O.R.; Snove, O.; Halaas, A.; Nedland, M.; Saetrom, P. (2006 IEEE International Conference on Cluster Computing, 2006)
Multiple instruction stream-single data stream (MISD) architectures have not found many practical applications in supercomputing. We present a multiple instruction stream-multiple data stream (MIMD) cluster implementation that uses MISD search processors with extreme pattern mining performance as a building block. We use PCI cards that hold sixteen search processors with local memory to build a relatively small cluster of five PC nodes with six PCI cards each. This cluster can handle anything between 64 independent queries at 48 GB per second, to 30,720 independent queries at 100 MB per second. The cluster's performance characteristics are such that we can easily scale the system to 10 15 operations per second with containable overhead using just 100 nodes. Further, the solution has lower power consumption and memory bandwidth requirements than comparable technologies.